Effects of light exposure during IVF: transcriptomic analysis of murine embryos and embryo-derived EVs - Nagy, Bence; Bognár, Zoltán; Csabai, Timea Judit; Fekete, Nóra; Buzás, Edit Irén; Kovács, Árpád Ferenc; Szekeres-Barthó, Júlia; Pállinger, Éva (Frontiers in Immunology, 2025)
IntroductionLight exposure of embryos during assisted reproduction affects embryo quality and implantation capacity in a wavelength dependent manner. We investigated the molecular mechanism of these light-induced changes through the comparative analysis of gene expression and regulatory miRNA profile of murine embryos cultured in dark environment and those exposed to white- or red filtered light. miRNA sequencing was used to assess the role of embryo-derived extracellular vesicles in the endometrium-embryo dialogue.MethodsIn vitro cultured mouse embryos at 3.5 days post coitum (dpc) were exposed to white or red filtered light. After 24 hours mRNA and miRNA content of the embryos as well as the miRNA content of embryo-derived extracellular vesicles were isolated and RNA-sequencing was performed. Differential expression analysis and functional enrichment analysis were used for evaluating the transcriptome results.ResultsLight exposure caused transcriptomic changes in the embryos. White light upregulated apoptotic pathways, while red filtered light gave rise to the activation of regeneration pathways, including DNA repair mechanisms. Embryo-derived extracellular vesicles enclosed wavelength dependently unique miRNA cargos the target genes of which play a role in embryo implantation.DiscussionWhite light upregulates apoptotic pathways, at both the transcriptome and regulatory miRNAs levels. Red filtration partially counterbalances these negative effects by shifting the cellular processes towards regeneration, including DNA repair mechanisms. Extracellular vesicles of light exposed embryos play a role in blastocyst-decidua communication through the horizontal transfer of regulatory miRNAs. Our data prove that light exposure during in vitro fertilization modifies cell function that might affect the outcome of implantation.